Does developmental timing of exposure to child maltreatment predict memory performance in adulthood? Results from a large, population-based sample. (January 2016) - Dunn, Erin C.; Busso, Daniel S.; Raffeld, Miriam R.; Smoller, Jordan W.; Nelson, Charles A.; Doyle, Alysa E.; Luk, Gigi
Abstract: Although maltreatment is a known risk factor for multiple adverse outcomes across the lifespan, its effects on cognitive development, especially memory, are poorly understood. Using data from a large, nationally representative sample of young adults (Add Health), we examined the effects of physical and sexual abuse on working and short-term memory in adulthood. We examined the association between exposure to maltreatment as well as its timing of first onset after adjusting for covariates. Of our sample, 16.50% of respondents were exposed to physical abuse and 4.36% to sexual abuse by age 17. An analysis comparing unexposed respondents to those exposed to physical or sexual abuse did not yield any significant differences in adult memory performance. However, two developmental time periods emerged as important for shaping memory following exposure to sexual abuse, but in opposite ways. Relative to non-exposed respondents, those exposed to sexual abuse during early childhood (ages 3–5), had better number recall and those first exposed during adolescence (ages 14–17) had worse number recall. However, other variables, including socioeconomic status, played a larger role (than maltreatment) on working and short-term memory. We conclude that a simple examination of "exposed" versus "unexposed" respondents may obscure potentially important within-group differences that are revealed by examining the effects of age at onset to maltreatment.